2006
DOI: 10.1007/s00109-006-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin(ogen) and its fragments in the pathophysiology and treatment of myocardial infarction

Abstract: The occlusion of a coronary artery leads to ischemia of the myocardium, while permanent occlusion results in cell death and myocardial dysfunction. Early restoration of blood flow is the only means to reduce or prevent myocardial necrosis, but-paradoxically-reperfusion itself contributes to injury of the heart. In animal models, this phenomenon is well described, and there are many different unrelated approaches to reduce reperfusion injury. In humans, however, pharmacological interventions have so far failed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
1
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 81 publications
1
90
1
2
Order By: Relevance
“…Both MoAbs T2G1 (anti-FgBb [15][16][17][18][19][20][21] ) and BV9 (anti-VE-cadherin EC3-EC4), but not MoAb 18C6 (anti-FPB Bb [1][2][3][4][5][6][7][8][9][10][11][12][13][14], partially inhibited Fg-induced FITCDextran Flux, implicating VE-cadherin and Fg-b in mechanisms of Fg-induced EC permeability. Fg is capable of inducing permeability of different types of barrier EC, as Fg also induced permeability of a microvascular EC barrier, whereas it did not induce permeability of an epithelial cell barrier.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both MoAbs T2G1 (anti-FgBb [15][16][17][18][19][20][21] ) and BV9 (anti-VE-cadherin EC3-EC4), but not MoAb 18C6 (anti-FPB Bb [1][2][3][4][5][6][7][8][9][10][11][12][13][14], partially inhibited Fg-induced FITCDextran Flux, implicating VE-cadherin and Fg-b in mechanisms of Fg-induced EC permeability. Fg is capable of inducing permeability of different types of barrier EC, as Fg also induced permeability of a microvascular EC barrier, whereas it did not induce permeability of an epithelial cell barrier.…”
Section: Discussionmentioning
confidence: 99%
“…14,[26][27][28] Control experiments indicated that Fg added to breast cancer or endothelial cells was not processed further by protease degradation or crosslinking to higher ordered structures (data not shown). Synthetic peptides corresponding to the Fg b-chain primary structure were custom synthesized as previously described, 11 and include b , b [15][16][17][18][19][20][21][22][23][24][25][26][27] , b 18-31 and b [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] (Table I). Fibrinopeptide A (Bachem) was used as a nonspecific peptide for permeability studies.…”
Section: Fibrinogen Purification and Synthetic Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 If bound to VEcadherin, fibrin fragments have open binding sites that can interact with leukocytes, which leads to endothelial attachment and transmigration. 13 B␤ is a breakdown product of fibrin that corresponds to the VE-cadherin binding sequence of the fibrin ␤-chain but which lacks the leukocyte binding site. 13 As a consequence, B␤ binding to VE-cadherin can competitively inhibit endothelial leukocyte adhesion.…”
mentioning
confidence: 99%